ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN UMKM JASA SERVIS SEPEDA MOTOR - Okvaldi, David Syafarudin; Prasetyo, Rian; Darsini, Darsini (KAIZEN : Management Systems & Industrial Engineering Journal, 2024)
As an economic growth, kind of human needs has become specifically. It is not only primary needs, but also secondary needs. Now, motorcycle has become human needs that basically everyone has it. As increase motorcycle users, repair services, also growth. This research is aim to find out effect of service quality on customers satisfaction in motorcycle service based on expectation and reality about tangibles, reliability, responsiveness, assurance and empathy for get priority attribute to improve. Importance Performance Analysis, and Customer Satisfaction Index method used in this research. Purposive sampling is used on 27 sample. IPA analysis found that services quality have a significant effect to customers satisfaction, based on 16 item questionnaire,it has 73,3%. It proves customers expectation didn’t match with reality. Furthermore, priority items that need to be fixed is tidiness and cleanliness, spare part and tool completeness, and on time of repairing.